2015
DOI: 10.5435/jaaos-d-15-00324
|View full text |Cite
|
Sign up to set email alerts
|

Readability of Orthopaedic Oncology-related Patient Education Materials Available on the Internet

Abstract: Online patient education materials related to orthopaedic oncology appear to be written at a level above the comprehension ability of the average patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…Our data suggest two main findings: that the average readability of online patient educational materials available through PM&R professional societies exceeds the recommended 8th‐grade level, and that approximately 17% of articles are written at or below this level, which is on par with the low frequency observed in readability analysis of orthopedic specialty websites . To our knowledge, this is the first study evaluating readability of PM&R patient education materials.…”
Section: Discussionmentioning
confidence: 56%
“…Our data suggest two main findings: that the average readability of online patient educational materials available through PM&R professional societies exceeds the recommended 8th‐grade level, and that approximately 17% of articles are written at or below this level, which is on par with the low frequency observed in readability analysis of orthopedic specialty websites . To our knowledge, this is the first study evaluating readability of PM&R patient education materials.…”
Section: Discussionmentioning
confidence: 56%
“…Ideally, a high-quality patient information website should be developed by a credible source and display accurate information regarding diagnostic tests, treatment options, outcomes, and possible complications. Information should also be at a reading level that is comprehensible to an average patient, as recent studies have shown patient materials on the Internet to be written at a much higher level than many patients can comprehend [ 18 20 , 22 ]. The OrthoInfo site ( www.orthoinfo.aaos.org ), created by the American Academy of Orthopaedic Surgeons (AAOS), scored among the top five websites for HON score and content completeness.…”
Section: Discussionmentioning
confidence: 99%
“…Video sources and uploaders were categorized as follows: (1) academic (pertaining to authors or uploaders affiliated with research groups, universities, or colleges); (2) physician (independent physician or physician group without research, university, or college affiliation); (3) nonphysician (health professionals other than licensed medical doctors); (4) trainer; (5) medical source (content or animations from health websites); (6) patient; and (7) commercial. Content was categorized as follows: (1) exercise training, (2) disease-specific information, (3) patient experience, (4) surgical technique or approach, (5) nonsurgical management, and (6) advertisement. The VPI is a calculation derived from the following formula: Like ratio  View ratio/100.…”
Section: Youtube Query and Video Characteristicsmentioning
confidence: 99%
“…However, many internet sources are not regulated or edited, resulting in the dissemination to patients of an overwhelming amount of content that may be low quality and inaccurate. [3][4][5][6] Therefore, it is imperative for physicians to be aware of and critically evaluate such resources to help educate patients and guide them through the management of their disease such that they are not misinformed.…”
mentioning
confidence: 99%